Rancang Bangun Aplikasi E-Monitoring Alat Perekam Transaksi Wajib Pajak Pada Kantor Badan Pengelola Pajak Dan Retribusi Daerah Kota Palangka Raya Berbasis Website - Zulfani, Muhammad; Oktaviyani, Enny Dwi; Licantik, Licantik (Journal of Information Technology and Computer Science, 2023)
The Office of the Regional Tax and Levy Management Agency often monitors or monitors the tax recording device used by the Taxpayer (WP). Sometimes the Taxpayer also reports by contacting the office via telephone. Based on this, an E-Monitoring Application for Taxpayer Transaction Recorder Tools was made at the Office of the Palangka Raya City Regional Tax and Retribution Management Agency Based on a Website to assist the office in monitoring and assisting Taxpayers to report constraints on tax recording devices. The methodology used in developing the E-Monitoring Application Design for Taxpayer Transaction Recorder Tools at the Office of the Regional Tax and Levy Management Agency of Palangka Raya City Based on this Website is using the Waterfall method. The stages are Requirements Definition such as making flowcharts, System and Software Design such as database design, Implementation and Unit Testing, namely the language used such as PHP, Javascript and Css, Integration and System Testing, which is testing using the black box testing method. The methodology used in the E-Monitoring Application of Taxpayer Transaction Recording Tools at the Office of the Regional Tax and Retribution Management Agency of Palangka Raya City Based on this Website is using the Waterfall method. The stages are Requirements Definition such as making flowcharts, System and Software Design such as database design, Implementation and Unit Testing Integration and System Testing and blackbox testing.The result of this research is an application of E-Monitoring Application of Taxpayer Transaction Recording Tool at the Office of the Regional Tax and Levy Management Agency of Palangka Raya City Based on a Website that can be used to report problems experienced by taxpayers in the use of taxpayer transaction recording devices and can assist the BPPRD to monitor the tool in case of damage and repair.